Addressing Corruption of Village Funds: A Perspective from Islamic Criminal Law and Positive Law on Asset Recovery - Firmansyah, Firmansyah; Kasma, Hadrawi; Rusdi, Mikdar (IAIN Manado, 2024)
Corruption in Indonesia is increasingly rampant, one of which is the issue of village funds, so the problem is analyzed, and problems are identified to resolve the case. The research method used is an empirical juridical approach using data collection techniques, namely in-depth interviews using qualitative descriptive analysis. The research results found that several things that cause corruption in village funds include low understanding, awareness, and supervision of the BPD (people's consultative body), lack of transparency and accountability, low community participation, political pressure and conflicts of interest, a culture of corruption, and the case studies raised to show that corruption occurs due to misuse by third parties and the efforts taken are based on This is an improvement on these 5 (five) aspects. The critical point is the offer from researchers regarding the reconstruction of the concept of asset recovery when it has been applied after going through the trial process. In this paper, we offer the idea of asset recovery outside of court based on an analysis of the cases raised.